Soil Compaction in the Urban Landscape - Amy L. Shober; Geoffrey C. Denny (EDIS)
SL317, a 4-page illustrated fact sheet by Amy L. Shober and Geoffrey C. Denny, discusses the problem of soil compaction, and methods for dealing with it. Published by the UF Department of Soil and Water Science, March 2010.